PENGARUH PENAMBAHAN ELISITOR METIL JASMONAT TERHADAP PERTUMBUHAN SERTA PRODUKSI STEVIOSIDA DAN REBAUDIOSIDA-A DARI KULTUR PUCUK STEVIA REBAUDIANA (BERTONI) PADA MIST BIOREACTOR - Emmanuel, Victor
Stevia rebaudiana leaves contain steviol glycoside compounds in the form of stevioside and rebaudioside-A which is 250-300 times sweeter than sucrose. More optimal propagation of S. rebaudiana can be done by in vitro propagation using a mist bioreactor. This study aimed to compare the growth of S. rebaudiana cultivated in a mist bioreactor with elicitor concentrations of methyl jasmonate 0 M (control) and 10 M, with the parameters of shoot addition, biomass addition, and relative growth rate, as well as a comparison of stevioside and rebaudioside concentrations. A. The shoot culture of S. rebaudiana in the control bioreactor showed an increase in the number of shoots by 4.7 times, biomass by 3.1 times, and a relative growth rate of 0.1. Meanwhile, shoot culture in mist bioreactor with elicitation treatment had better growth, with a 4.9-fold increase in the number of shoots, a 5.5-fold increase in biomass, and a relative growth rate of 0.13. The stevioside content of S. rebaudiana culture in the control bioreactor was higher at 1,157.52 ?g/g dry weight (DW), compared to the bioreactor with the addition of 10 M methyl jasmonate as much as 746.91 ?g/g DW. However, the rebaudioside-A content in the control bioreactor was lower at 101.86 ?g/g DW, compared to the bioreactor with elicitation of 142.52 ?g/g DW.